Angiolipoleiomyoma of the Uterus with a Dermoid Cyst in the Right Ovary: An Unusual Association - Deepika Gupta; Purnima Malhotra; Seema Rahar; Arvind Ahuja (Wolters Kluwer Medknow Publications, 2024)
Angiolipoleiomyoma is a benign mesenchymal mass composed of smooth muscle, mature adipose tissue, and abnormal blood vessels. It is rarely diagnosed in uterine masses and its prevalence among benign uterine lesions is 0.06%. We report the case of a 40-year-old female presenting with a complaint of heavy menstrual bleeding. Computed tomography scan revealed a large uterine mass with the right ovarian cyst. Histopathological examination confirmed the nature of the lesion as a benign angiolipoleiomyoma with a dermoid cyst of the right ovary. This rare association is reported to apprise gynecologists to consider this unusual tumor during the management of uterine masses.